34.1: Invited Paper: Availability of a‐IGZO semiconductor TFT in the large size Gen. 11 facilities for competitive high‐end applications. (26th August 2021) - Seo, Hyun-Sik; Sun, Qianhui; Wu, Wei; Hsu, Yuan-Jun; Li, Shan; Cao, Weiran; Xiao, Jun Cheng; Wu, Yuan-Chun; Zhao, Bin; Zhang, Xin; Yan, Xiaolin
Abstract : We investigated the four‐phase amorphous‐InGaZnO (a‐IGZO) thin film transistors (TFTs) in the world largest generation 11 factory (Gen.11, 2940mm × 3370mm) which has the cost advantage for future high‐end applications compared to generation 8.5 (Gen. 8.5, 2200mm × 2500mm). Self‐aligned coplanar structure TFT has been developed for large size inkjet printing (IJP) OLED display, and 4 mask back channel etched (BCE) type TFT has been developed for large size 8K4K LCD applications. For the purpose of low cost, high‐end applications, the availability of large size oxide TFT is essential in Gen. 11.